Identifying At-Risk Patients with Pediatric Intracranial Steno-Occlusive Arterial Disease: A 10-Year Experience. (16th November 2020) - Nguyen, Vincent; Khan, Nickalus; Diaz, Jorge Lee; Klimo, Paul; Choudhri, Asim; Vaughn, Brandy; Hersh, David S; Elijovich, Lucas; Motiwala, Mustafa
Abstract: INTRODUCTION: Non-traumatic pediatric intracranial steno-occlusive arterial disease (ISAD) includes a number of distinct entities (inherited or acquired), most notably true moyamoya or moyamoya-like vasculopathy. Children with ISAD are managed either medically alone, typically in the form of antiplatelet therapy, or with surgical revascularization in conjunction with medical therapy. However, there is no accepted protocol to determine the choice of treatment. METHODS: Children with ISAD were identified using several institutional databases. Eligible patients were those less than 21 years of age and had undergone both a customized moyamoya magnetic resonance imaging (MRI) protocolin conjunction with a conventional cerebral angiogram. The primary goal of the workup was to assess cerebral perfusion and to identify "at-risk" parenchyma. The key component is the combination of a 3-phase arterial spin label (ASL) with cerebral blood flow seen on angiography.All imaging and clinical information in turn was used to determine treatment allocation into either medical or surgical management. The results of our workup, treatment and clinical outcomes were evaluated. RESULTS: Forty-seven patients with 61 affected hemispheres were identified over a 10-year period (2010 to 2020). The average age was 10 years (range, 6.8 months-20.2 years), with almost equal distribution of males and females (24 males, 24 females). There was a statistically significant difference between those patients with incomplete or complete collaterals on angiography and the different ASL categories ( P < . 02, Kruskal-Wallis). There were 29 (48%) cases that received surgery upfront and 32 (52%) cases that were initially managed medically. There was a statistically significant difference in the proportion of patients who had a normal ASL and received surgery or medical management ( P < . 01, Chi-Square). There was also a statistically significant difference in the proportion of patients that received medical or surgical management with complete ( P < . 03, Chi-Square) or incomplete ( P < . 01, Chi-Square) collateralization on angiography. CONCLUSION: An algorithm of MRI, 3 phase ASL, and angiography can help differentiate patients who will benefit from revascularization surgery from those who can be observed.